2016
DOI: 10.1016/j.cplett.2016.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics limits the reactivity of BrHg radical with volatile organic compounds

Abstract: Mercury emissions to the atmosphere primarily consist of Hg(0), which tends not to enter ecosystems until it is oxidized. Atomic bromine initiates oxidation of Hg(0) via the BrHg• intermediate, but the further reactions of BrHg• are just beginning to be explored. Here we use quantum chemistry to determine that hydrogen abstraction from hydrocarbons by BrHg• is so endothermic as to be irrelevant. Bonds between BrHg• and carbon atoms are so weak that BrHg• addition to carbon-carbon double bonds atoms will be som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…1 shows the main reactions for thermal and photochemical conversion between Hg 0 , Hg I , and Hg II species ( 25 ). syn -HgBrONO and HgBrOOH are considered the major gaseous oxidized Hg II species from Br-initiated two-step Hg 0 oxidation ( 6 , 26 , 27 ). It has been calculated that following gas-phase photolysis, syn -HgBrONO breaks down to HgBrO (90%) and HgBr (10%) ( 24 , 25 ), and HgBrOOH yields Hg 0 (66%), HgBrO (31%), and HgBr (3%) ( 25 ).…”
Section: Chemical Mechanisms and Global Model Simulationsmentioning
confidence: 99%
“…1 shows the main reactions for thermal and photochemical conversion between Hg 0 , Hg I , and Hg II species ( 25 ). syn -HgBrONO and HgBrOOH are considered the major gaseous oxidized Hg II species from Br-initiated two-step Hg 0 oxidation ( 6 , 26 , 27 ). It has been calculated that following gas-phase photolysis, syn -HgBrONO breaks down to HgBrO (90%) and HgBr (10%) ( 24 , 25 ), and HgBrOOH yields Hg 0 (66%), HgBrO (31%), and HgBr (3%) ( 25 ).…”
Section: Chemical Mechanisms and Global Model Simulationsmentioning
confidence: 99%
“…As we showed, the weakness of the BrHg-CH2CH2• bond means that this radical will dissociate before undergoing any bimolecular collisions. 73 Given the higher barrier and lesser stability of the products in the HOHg• + CH2=CH2 reaction, we suggests that HOHg• addition to alkenes will be very inefficient.…”
Section: Y Pbe0 Ccsd(t)//pbe0mentioning
confidence: 88%
“…Our study 73 of the BrHg• + CH2=CH2 reaction showed that, like OH + CH2=CH2, this reaction proceeds by a barrierless formation of a van der Waals complex, which then passes over a transition state to form BrHgCH2CH2•. Figure 5 depicts the potential energy profile for the analogous HOHg• + ethylene system at PBE0/AVTZ.…”
Section: Y Pbe0 Ccsd(t)//pbe0mentioning
confidence: 96%
“…It has previously been suggested that syn ‐HgBrONO and HgBrOOH are the major gaseous oxidized mercury compounds from the reaction of Hg 0 with Br atoms . Previous computational studies have focused mainly on the thermal reactivity of closed‐shell molecules .…”
Section: Introductionmentioning
confidence: 99%